2017
DOI: 10.1007/s00296-017-3723-4
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the 12-item WHODAS 2.0 in patients with Kashin–Beck disease

Abstract: The purpose of this study was to check the reliability and validity of the 12-item Chinese version of the World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) for the assessment of disability in patients with Kashin-Beck disease (KBD). We recruited 219 patients with KBD from the high-risk KBD area in the Shaanxi province, using stratified multistage random sampling. We assessed each patient using the Chinese version of the 12-item WHODAS 2.0 and the Western Ontario and McMaster Universitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…It was confirmed that the Polish version of the tool was consistent over time (ICC value of 0.91). Younus et al also confirmed the very good repeatability of the 12-item WHODAS 2.0 [ 34 ], and likewise, good consistency over time (1 week) was also affirmed by Moreira et al, who used the test–retest method and obtained an ICC of 0.77 [ 37 ]. Similar test–retest values (ICC value of 0.88) were obtained by Marom et al [ 38 ].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It was confirmed that the Polish version of the tool was consistent over time (ICC value of 0.91). Younus et al also confirmed the very good repeatability of the 12-item WHODAS 2.0 [ 34 ], and likewise, good consistency over time (1 week) was also affirmed by Moreira et al, who used the test–retest method and obtained an ICC of 0.77 [ 37 ]. Similar test–retest values (ICC value of 0.88) were obtained by Marom et al [ 38 ].…”
Section: Discussionmentioning
confidence: 76%
“…In addition, Carlozzi et al, examining disability using the 12-item WHODAS 2.0 among people with Huntington's disease, obtained a Cronbach's α value for the entire tool of 0.94, and for individual domains, Cronbach's α ranged from 0.74 to 0.90 [28]. Younus et al, studying the psychometric values of the 12-item WHODAS 2.0 in patients with Kashin-Beck disease obtained Cronbach's α values for individual domains ranging from 0.70 to 0.91 [34]. Axelsson et al also confirmed the high scale score reliability of the 12-item WHODAS 2.0 in patients with anxiety and stress disorders (Cronbach's α values were in the range of 0.83-0.92) [35].…”
Section: Discussionmentioning
confidence: 99%
“…A complex scoring method was used, in which the scores within each domain and all six domains were summed and converted to an overall score ranging from 0 to 100 (0 = no disability; 100 = full disability). We used the Chinese version of the 12-item WHODAS 2.0 [25], and the Cronbach's alpha and ICCs for the six domains in KBD patients ranged from 0.70 to 0.91 and 0.69 to 0.85, respectively [12].…”
Section: Assessment Questionnairesmentioning
confidence: 99%
“…a A representative patient severely affected with KBD (female, 57 years old, height 102 cm), which manifested as deformed and shortened fingers, a short stature and limited motion of the joints in the extremities. b & c Images and radiographic images of the bilateral hands of this patient, showing deformed fingers and metaphyseal lesions in the phalanges joint dysfunction index (JDI) [11] and the 12-item World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) [12]. The WOMAC is a well-known self-administered instrument that was developed for the assessment of hip and knee osteoarthritis [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation